CFD study of Thermal Runaway in a Battery Module - Lindblad, Eric (My University, 2024)
To fight climate change and decrease emissions battery powered electric vehicles are becoming more common. These vehicles often use lithium-ion batteries which if subject to extreme conditions can enter thermal runaway, a violent exothermic reaction that spreads between battery cells releasing energy in the form of heat and gases. This poses serious safety risks for the occupants of the vehicle and is something automotive manufacturers are trying to find ways to mitigate. In this thesis thermal runaway is simulated using computational fluid dynamics to predict the propagation time between battery cells within a battery module. The commercial software Star-CCM+ was used to perform the simulations which included both built in and user created methods for capturing the behaviour of thermal runaway. After results for a baseline case were obtained two different mitigation strategies were implemented, one with cooling and one with improved insulation between the battery cells. It was found that the methods used is this thesis can be implemented to simulate thermal runaway and to predict its propagation. A large portion of the heat released from each battery cell during thermal runaway was observed to be transported into the cooling plate, increasing the temperature of the neighboring cells. The hot gases released spread all throughout the battery module transferring heat to all battery cells. The mitigation strategies were both found to delay the propagation of thermal runaway with cooling being more effective delaying thermal runaway in the last battery cell by 18 seconds.
Keywords: CFD; Thermal Runaway; Battery; Lithium-ion; Turbulence modelling; Heat transfer; Star-CCM+